Reptiles and amphibians - O’Shea, Mark (DK Pub., 2001)
A systematic approach, authoritative text, and clear photographs make the Dorling Kindersley Handbook of Reptiles and Amphibians the most comprehensive and easy-to-use pocket guide to the reptiles and amphibians of the world. Packed with over 600 color photographs of more than 400 species, this handbook is designed to enable you to recognize each species quickly and easily. Expertly written, each entry combines a precise description with fully annotated photographs to highlight the chief characteristics and distinguishing features of each species. A comprehensive introduction describes the anatomy, lifecycle, and behavior of the major groups of reptiles and amphibians, while the initial steps of identification are facilitated by a clear visual key. Each entry in the Dorling Kindersley Handbook of Reptiles and Amphibians is accompanied by a map showing the geographical distribution of the species while the text and color-coded bands give the internationally accepted scientific name and provide at-a-glance information on size, diet, habitat, reproduction, and population status.